Identity of the oribatid mite Oribata curva and transfer to Trichogalumna (Acari, Oribatida, Galumnidae), with discussion of nomenclatural and biogeographical issues in the ‘curva’ species-group - Norton, Roy A.; Ermilov, Sergey G. (Zootaxa, 2017)
Based on the study of type material, other historical specimens, and new collections, the adult of the thelytokous oribatid mite Oribata curva Ewing, 1907 (Galumnidae) is redescribed and the name is recombined to Trichogalumna curva (Ewing, 1907) comb. nov. A confusing history of synonymies and misidentifications is traced in detail, and their effect on published statements about biogeography is assessed. Reliable records of T. curva are only those from North America. The tropical mite Pergalumna ventralis (Willmann, 1932) is not a subspecies of T. curva. The widely-reported Trichogalumna nipponica (Aoki, 1966) and other similar species form a complex with T. curva that needs further morphological and molecular assessment.